2017
DOI: 10.1155/2017/3573082
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Immune Checkpoints, Immune System, and BCG in the Treatment of Superficial Bladder Cancer

Abstract: This paper aims to study the dynamics of immune suppressors/checkpoints, immune system, and BCG in the treatment of superficial bladder cancer. Programmed cell death protein-1 (PD-1), cytotoxic T-lymphocyte-associated antigen 4 (CTLA4), and transforming growth factor-beta (TGF-β) are some of the examples of immune suppressors/checkpoints. They are responsible for deactivating the immune system and enhancing immunological tolerance. Moreover, they categorically downregulate and suppress the immune system by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These pathways are crucial for self-tolerance and innate immunity and prevent the immune system from attacking cells indiscriminately (2). Immune checkpoints consist of stimulatory checkpoint molecules and inhibitory checkpoint molecules (7,8). Inhibitory checkpoint molecules have been considered important targets for cancer immunotherapy (9).…”
Section: Introductionmentioning
confidence: 99%
“…These pathways are crucial for self-tolerance and innate immunity and prevent the immune system from attacking cells indiscriminately (2). Immune checkpoints consist of stimulatory checkpoint molecules and inhibitory checkpoint molecules (7,8). Inhibitory checkpoint molecules have been considered important targets for cancer immunotherapy (9).…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoints are immune system negative regulators that play crucial roles in maintaining self-tolerance, avoiding autoimmunity, and protecting tissues from immune collateral harm. [29] In cancer, immune checkpoints had a critical role in the tumor-related immune Table 2 In GC samples, the correlations between the immune cell marker genes and NT5DC2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoints were negative regulators in immune system. They participated in the prevented autoimmunity and protected tissues from immune damage 47 . It has been demonstrated that inhibition of immune checkpoints could enhance the anti-tumor immunity in cancers 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%